Review of Agility and Power Performance between Gender in Muay Thai Athletes - Shapie, Muhamad Nizam Mohamad; Sani, Muhammad Haziq Mat; Ihsan, Nurul; Okilanda, Ardo; Haryanto, Jeki; Samsudin, Hazim; Nawai, Nasru Syazwan (International Martial Arts and Culture Journal, 2023)
Background and aim. This paper aims to provide a comprehensive review of gender differences among Muay Thai (MT) athletes, covering aspects such as definition, injury risk, gender issues, gender recognition, fitness components, motivation factors, agility and power performance, instrumentation, training, and previous research. It also compares agility and power performance between male and female athletes to examine their effectiveness.Methods.  This study employs a literature review approach by analyzing and synthesizing previous studies related to Muay Thai athletes, with a focus on gender perspectives and performance components.Results.  The findings indicate that agility enables rapid directional changes without compromising balance and precision, while power, defined as the combination of speed and force, is positively correlated with agility performance. Gender dynamics in Muay Thai highlight ongoing debates regarding opportunities for female athletes and the influence of physiological differences. In addition, the literature reveals a scarcity of research on Muay Thai in Malaysia, particularly in terms of fitness and body conditioning.Conclusions. This study provides important insights for stakeholders in promoting Muay Thai and guiding athlete development. It also contributes to a broader understanding of gender perspectives in Muay Thai, supporting its growth and future development.